(untitled) (American Journal of Islam and Society, 2008)
A colloquium on “girl studies,” organized by Marcia Hermansen (director, IslamicWorld Studies) and Laura Miller (professor, Department of Anthropology) took place on 12 April 2008, at Loyola University Chicago. Presently, the study of adolescent females – increasingly referred to as girl studies – as a separate realm of focus is a contested idea in academe. Supporters claim that girl studies is a worthwhile research domain due to the prior disregard for age within women’s studies and gender within youth studies. Detractors note that the category and boundaries of what is considered a “girl” are unstable and historically and culturally varied. More specifically, such scholars as Sharon R. Mazzarella, Norma Odom Pecora, and Catherine Driscoll have argued that over time, literature, popular reading, and consumerism have become the means through which the mainstream culture instructs girls on how to become women. In turn, many girls negotiate their interests, sexual expression, body image, and rites of passage in culturally approved ways. Other girls, however, engage in personal, subjective interpretation by rejecting hegemonic standards of femininity in a post-industrial western world and often in the context of violence, displacement, and resistance. Loyola’s conference highlighted the impact of mainstream norms and ethnocentrism in girl studies by including scholarship from a range of American and non-American cultural contexts. We investigated how girls’ lives are constructed in an era of massive change as communities around the world experience processes of both globalization and localization ...